Marketing Management of Educational Services in Early Childhood Education - Sulistyorini Sulistyorini (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The number of PAUD institutions has increased very significantly. This makes each institution have to compete and devise a strategy to win the hearts of parents of prospective students. This study aims to analyze the marketing strategy of educational services carried out by PAUD institutions to parents of prospective students. The research used a descriptive qualitative approach, the researchers conducted observations and interviews with teachers, parents, and community leaders in 3 PAUD institutions in Tulungagung Regency. The respondents in this study were selected using a purposive sampling technique based on the criteria set by the researcher. The results of the study show that PAUD institutions are aware of the urgency of marketing management. Various elements such as teachers, student guardians and stakeholders synergize in marketing educational services. Among the implications of this research is the importance of resources in educational institutions having the ability to manage the marketing of educational services. This ability will increase competitiveness, sustainability of institutions and the quality of graduates.